2003
DOI: 10.1097/01.rlu.0000079390.72098.b2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Rapid (Accelerated) Gastric Emptying

Abstract: RGE has no relationship to age or gender. RGE may be representative of early dumping syndrome in most patients. GES help make a clear distinction between early dumping syndrome and gastroparesis, which can present with similar symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…Although we used more stringent criteria to define rapid GE and excluded patients who had prior gastric surgery, this proportion is comparable to the prevalence (ie, 10% of 750 patients, 9% of 545 patients, and 9% of 2907 patients) in earlier reports that included patients who had gastric surgery. 3,10,28 In another study, 28% of 642 patients undergoing scintigraphy had rapid GE, perhaps because a less stringent criterion was used to define rapid GE (ie, gastric half-emptying time less than 70 minutes). 29 Nearly, one-third of patients with rapid GE1 had nausea and/or vomiting, perhaps because rapid delivery of nutrients distends and Only insulin therapy* 89 (59) 9 (33)…”
Section: Discussionmentioning
confidence: 99%
“…Although we used more stringent criteria to define rapid GE and excluded patients who had prior gastric surgery, this proportion is comparable to the prevalence (ie, 10% of 750 patients, 9% of 545 patients, and 9% of 2907 patients) in earlier reports that included patients who had gastric surgery. 3,10,28 In another study, 28% of 642 patients undergoing scintigraphy had rapid GE, perhaps because a less stringent criterion was used to define rapid GE (ie, gastric half-emptying time less than 70 minutes). 29 Nearly, one-third of patients with rapid GE1 had nausea and/or vomiting, perhaps because rapid delivery of nutrients distends and Only insulin therapy* 89 (59) 9 (33)…”
Section: Discussionmentioning
confidence: 99%
“…This finding is, however, in accordance with a recent study by Singh et al in which a 79-kcal meal consisting of only one radiolabeled egg and no unlabeled carbohydrate portions was administered. 1 In the Singh study, 10.7% of patients referred for gastric emptying studies as a result of gastrointestinal complaints were found to have rapid gastric emptying.…”
Section: Discussionmentioning
confidence: 98%
“…Generally these symptoms have been previously assumed to be associated with delayed gastric emptying, although a recent article has reported that rapid gastric emptying occurs frequently in patients with these complaints. 1 On the other hand, patients with diabetes, prediabetes, and other manifestations of insulin resistance or the metabolic syndrome have been described as having rapid gastric emptying of carbohydrate-containing solid and liquid meals. [2][3][4][5][6] Many different types of meals have been described for use in clinical nuclear medicine studies, including a hamburger meal, 7 a standardized egg white and toast meal, 8 a pancake meal, 9 a mashed potato meal, 10 and a corn flakes and milk meal.…”
mentioning
confidence: 99%
“…Patients with recent onset diabetes mellitus may exhibit accelerated GET of liquids and solids that has not been correlated to neuronal dysfunction but, rather, increased phasic motor activity in the gastric fundus in these patients, suggesting a motor abnormality in this region [28][29][30][31][32]. Although accelerated gastric emptying was initially attributed to the early stages of diabetes mellitus, there are the studies showing that it can be associated with late diabetes mellitus [33]. The working hypothesis is that the rapid gastric emptying of early diabetes represents vagal nerve damage from diabetes and, hence, impaired relaxation of the fundus.…”
Section: Discussionmentioning
confidence: 99%